Persuasive technique analysis of jakarta post daily e-paper - Novionita, Made Linda; Jayantini, I Gusti Agung Sri Rwa; Suastini, Ni Wayan (Institut Pariwisata dan Bisnis Internasional, 2021)
In this era, the news is a medium to share the information and some newspaper companies had already made the E-Paper. There are some problems discussed in this article such as the type of persuasive technique and its function used in The Jakarta Post daily e-paper and meaning consists in the persuasive technique. The collected data were analyzed by applying descriptive qualitative method. In the analysis, persuasive language technique and its function were comprehensively analyzed based on theory from Walton (2005) and the meaning used theory from Leech (1981). There were seven types of persuasive language techniques found in The Jakarta Post daily e-paper. The use of adjective is a persuasive language technique that is often used in The Jakarta Post’s news that published on 21st September 2020 until 25th November 2020.